2014
DOI: 10.1097/01.ogx.0000445771.22049.b2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cervical Lengths Using Transabdominal and Transvaginal Sonography in Midpregnancy

Abstract: Rates of preterm birth have increased in recent years, and the focus is now on primary prevention. Both transvaginal (TV) sonography and transabdominal (TA) sonography are used to assess cervical length. Many factors, including the mother's physical condition and fetal position, influence the practical use of TA sonography. This retrospective study 126Obstetrical and Gynecological Survey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our findings were keeping in line with findings of other similar studies 8,11,13,14 . Spearman correlation coefficient demonstrated a positive association between all three measurements.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings were keeping in line with findings of other similar studies 8,11,13,14 . Spearman correlation coefficient demonstrated a positive association between all three measurements.…”
Section: Discussionsupporting
confidence: 94%
“…[19][20][21] Likewise, one study reported that measurements obtained through TAUS are 8 mm longer on average than those obtained through TVUS, whereas another study showed excellent correlation between the 2 techniques. 22,23 In the setting of such a discrepancy, it is probably most prudent to either forego TAUS for this purpose or to have a low threshold to follow-up with TVUS if the measurement obtained abdominally is <30 mm.…”
Section: The Techniquementioning
confidence: 98%
“…Roh et al and Stone et al both found no difference in mean cervical lengths between TA and TV measurements. 12,13 They found that TA cervical lengths consistently measured shorter than the TV measurements in cases with discrepancies. In contrast, Hernandez-Andrade et al found that only 43% of women with a short cervix on TV ultrasound were correctly identified by TA ultrasound and that TA ultrasound overestimated the cervical length in women with a short cervix.…”
Section: Discussionmentioning
confidence: 98%